Meaning, Absurdity, and Euphemisms - Stepanov, Jurij (Respectus Philologicus, 2003)
The article deals with different meanings of euphemisms and their relation to the categories of meaning and absurd. Euphemism is defined as an indirect representation of a situation when unpleasant or indecent characteristics are suppressed. However, the euphemism used in its broad meaning is understood as a general description of the creative process: if it is impossible to change the situation in real life, i.e. in material life, then it is possible to do that in mental life having depicted it in a certain way. The article analyses the creative concept of euphemism in different aspects and various fragments. Euphemisms as mental ways of reality re-creation are studied in poetry and rituals. Besides, their common characteristics are pointed out and new euphemisms are described as an expression of absurd.